Research ethics and policy implications for stem cell technology in Malaysia / Nishakanthi Gopalan - Nishakanthi , Gopalan (2018)
Stem cell research and technologies are revolutionizing regenerative medicine tremendously. In Malaysia, the research has improved in the last decade resulting in significant publications and clinical trials, but merely overseen by the Guideline for Stem Cell Research and Therapy 2009 which was formulated originally in 2006. There is no legislation or regulatory policies enacted to regulate the whole subject area. While previous studies in Malaysia highlighted the ethical issues of stem cell research from a religious viewpoint, this study focuses on the ethical aspect and policy implication of stem cell technology in Malaysia. It aims to study the status and the current regulatory processes of the Malaysian stem cell research and technologies, to discuss the needs and implications of the stem cell policy and, to explore the ethical perspectives of the international and Malaysian authors. This study is significant as it emphasizes the primary issue of stem cell research and its technologies that is, the absence of an effective policy to regulate its practices. Data for this study were obtained through in-depth interviews with relevant experts including scientists, ethicists, and policymakers as well as library research to analyze both international and Malaysian authored publications. This study found that stem cell research is unregulated in Malaysia and this caused worries among scientists to conduct research more efficiently, formally and openly, which in turn delaying the progress of this field as a whole. The current stem cell guideline is insufficient to prevent the unethical conducts which notably involves the private sector of stem cell technologies, identified in this study as grey area or regulatory loopholes. Without a legal stature, it is ineffective in capturing non-compliances, formal complaints or whistleblowing, unlike a regulatory policy. The study also reveals red-tape bureaucracies, interchanging directors with different instructions and religious issues are the main challenges faced by the Malaysian policymakers in devising a permanent regulatory framework for better management of stem cell technologies in Malaysia. Since Malaysian experts are accustomed to incorporate religious norms into their ethical inquiries and policymaking, it is vital to devise a framework that suits multi-religious setting, or significantly improve any globally available model they hope to adopt. The formulation of research and development (R&D) regulatory policies is very important in terms of its effectiveness in regulating and managing the national stem cell technology and other similar innovations in the future.